PENYERAPAN TENAGA KERJA SEKTORAL MENURUT SIFAT PRODUKSI SEKTOR EKONOMI DI BALI - Mutiara, Citra Chintia; Bendesa, I K G (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
The increase of tertiary sector GDP and the decline of primary sector GDP indicate that there was a shift of economic structure from primary to tertiary. The contribution to GDP and the proportion of workforce of Agriculture Sector has decreased but its productivity is increasing. This condition indicates there is over supply of labor in the Agriculture Sector. The first object of this study is to analyze the nature of the production sector of the economy of Bali today, labor intensive or capital intensive. While the second object is to analyze the influence of age, level of education, gender, number of working hours, and long years of works on employment opportunities to work in labor intensive sectors. Result of analysis with Cobb-Douglas shows nine sectors of economy in Bali are labor intensive sectors due to the elasticity of labor in each sectors is greather than the elasticity of investment. The analysis of the relationship several variables of labor to employment opportunities in labor intensive sectors indicates the age, level of education, gender, number of working hours, and long years of work significantly affect employment opportunities to work in labor intensive sectors.
Keywords: capital intensive, labor intensive, Cobb-Douglas, Binary Logistic Regression